In-situ hydrogenation of dual function material for integrated CO2 capture and methanation with the presence of steam - Daocheng Liu; Liangyong Chen (Carbon Capture Science & Technology)
The impacts of steam on hydrogenation of dual function materials (DFM) for Integrated CO2 Capture and in-situ methanation (ICCM) is a new area requiring detailed investigations prior to industrialization. This work investigated impacts from steams on hydrogenation of Ru-Na2CO3/γ-Al2O3 DFM for ICCM that containing Na2O adsorbent, Ru sites, and γ-Al2O3 support. DFM performance was examined in cyclic reactions as introducing external steam during hydrogenation, and the behaviors of adsorbed CO2 species during hydrogenation were characterized by in-situ DRIFTS and H2-TPSR. CH₄ selectivity decreased sharply from 84.3 % to 1.2 % as increasing external steam concentrations to 20 vol.%, and the conversion of adsorbent component decreased from 298.5 μmol g-1 to 167.1 μmol g-1. b-CO32- and m-CO32- formed at Na2CO3/γ-Al2O3 interface were the carbonate species that could be hydrogenated into CH4, some of which were desorbed into CO2 due to moisture-driven desorption effects. With the presence of external steam in H2 reactants, the conversion of carbonate species is a competing process between hydrogenation and moisture-driven desorption. In ICCM reaction with external steam present, b-CO32- was preferred to be desorbed into CO2; while for m-CO32-, desorption into CO2 by steam and hydrogenation into CH4 proceeded in parallel. Strong moisture-driven desorption effects from steam product were demonstrated in a fixed-bed reactor, which also led to rapid decrease of localized selectivity of CH4 along bed height.